Supramolecular Self-Assembled Nanostructures for Cancer Immunotherapy - Huang, Zichao; Song, Wantong; Chen, Xuesi (Frontiers in Chemistry, 2020)
Functional materials and nanostructures have been widely applied for enhancing the therapeutic potency and safety of current cancer immunotherapy. While profound of nanostructures have been developed for participating the development of cancer immunotherapy, constructing intricate nanostructures with easy fabrication and functionalization properties for satisfying the diversified requirements in cancer immunotherapy is highly required. Hierarchical self-assembly exploiting supramolecular interactions to manufacture organized architectures at multiple length scales represents an interesting and promising way for sophisticated nanostructures construction. In this mini-review, we will outline the recent progress in the development of supramolecular self-assembled nanostructures for cancer immunotherapy, with special focus on the supramolecular interactions including supramolecular peptide assembly, supramolecular DNA assembly, lipid hydrophobic assembly, host-guest assembly, and biomolecular recognition assembly.